Methods of presenting formulated requirements to the information system at the level of knowledge - Евланов, Максим Викторович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents research findings on the methods of presenting formulated functional requirements to the information system at the level of knowledge. The approaches developed in the study are as follows: a method of presenting functional requirements at the level of knowledge of an individual participant of the automated process, a method of presenting functional requirements at the level of knowledge of the Consumer of IT services, a method of presenting functional requirements at the level of knowledge of the Provider of IT services, and a method of presenting functional requirements at the level of system-wide knowledge. The developed methods allow automation of the processes of presenting and analysing functional requirements to information systems. With the help of these methods, the task of matching the requirements of the Consumer with those of the Provider of IT services can be viewed as the task of creating a system-wide presentation of requirements at the level of knowledge. This considerably simplifies the solution of the problem of synthesis in the descriptions of the rational architecture of the information system. The devised methods and the thereby resulting tools of developing information systems unify and simplify the processes of pre-surveying and designing information systems. This, in turn, helps reduce the cost and time of implementing IT projects for creation and upgrading of information systems. Moreover, the use of the developed methods allows the Provider to adapt previously obtained solutions to the peculiarities of the new requirements of the Consumer.